VD_FINDINFO Jug / 2015 / 167 vom 22. April 2015 - VD Tribunal cantonal (2015)
VIOLENCE CONTRE LES AUTORITÉS, FIXATION DE LA PEINE, SURSIS PARTIEL À L'EXÉCUTION DE LA PEINE | 285 CP, 42 CP, 43 CP, 47 CP